1991
DOI: 10.1093/jnci/83.19.1386
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Drug Resistance in a Human Colon Cancer Xenograft Expressing MDR1 Complementary DNA by In Vivo Administration of MRK-16 Monoclonal Antibody

Abstract: One strategy to overcome multidrug resistance in neoplasia is to inhibit the gp170 glycoprotein (relative molecular mass, 170,000) that functions as a plasma membrane, energy-dependent, drug-efflux pump. The human colon cancer cell line HT-29, which grows as an ascitic tumor in athymic NCr-nu/nu nude mice, was made multidrug resistant by infection with an MDR1 (also known as PGY1) retrovirus. Referred to as HT-29mdr1, it was used to study reversal of drug resistance in vivo by the anti-P-glycoprotein monoclona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Another mode of MDR reversal utilises monoclonal antibodies, several of which inhibit P-gp-mediated drug effl ux in vitro [90,91] . For in vivo applications, compa- Various other means of circumventing resistance that are being explored are based on experimental observations described above: these include adjuvant treatment with suramin to reverse fi broblast growth factor-mediated resistance [85] ; inhibition of p13 kinase/Akt to prevent resistance mediated through integrin involvement, and re-expression of wild-type tumour suppressor genes.…”
Section: Approaches To Overcoming Drug Resistancementioning
confidence: 99%
“…Another mode of MDR reversal utilises monoclonal antibodies, several of which inhibit P-gp-mediated drug effl ux in vitro [90,91] . For in vivo applications, compa- Various other means of circumventing resistance that are being explored are based on experimental observations described above: these include adjuvant treatment with suramin to reverse fi broblast growth factor-mediated resistance [85] ; inhibition of p13 kinase/Akt to prevent resistance mediated through integrin involvement, and re-expression of wild-type tumour suppressor genes.…”
Section: Approaches To Overcoming Drug Resistancementioning
confidence: 99%
“…These investigators found that treatment of some MDR cell lines with a monoclonal antibody (mAb) MRK16 increased intracellular accumulation and cytotoxicity of vincristine and actinomycin D. MRK16 also increased the in vivo toxicity of vincristine to a human MDR cell line grown as a xenograft in nude mice (13). The in vitro potentiation of drug cytotoxicity by MRK16, however, was weak relative to that of chemical inhibitors and was apparently limited to only some of the Pgp substrates, since MRK16 had no effect on doxorubicin cytotoxicity (12).…”
mentioning
confidence: 99%
“…Initially, these antibodies were intended to study the membrane changes in MDR cells, but later research demonstrated that MRK-16 was able to inhibit P-gp mediated efflux of vincristine and actinomycin D in vivo [172,173] . The addition of a P-gp inhibitor such as cyclosporine A to MRK-16 treatment, further sensitized MDR myelogenous leukemia cells to vincristine and doxorubicin [174,175] .…”
Section: Monoclonal Antibodies Against P-gpmentioning
confidence: 99%